Gold price and its relationship with U.S. macroeconomics variables / Sheikh Muhammad Hiffni Sheikh Mohd Fauzi - Sheikh Mohd Fauzi, Sheikh Muhammad Hiffni (2012)
This research paper is focused to study the relationship of gold price and U.S. macroeconomics variables which are US Dollar Index, US Inflation Rate and US Interest Rate. The reason is because in last decade, gold price has soared and reached its new high. This study used descriptive analysis and empirical analysis to know the relationship. As overall, there are significant relationships between US Dollar Index and US Interest Rate with gold price while no significant relationship found in US Inflation Rate.